Operation Youth Success (Douglas County Collective Impact) Developmental Evaluation Report - Miller, Jennifer L. (2016)
In the summer of 2014, a subset of leaders and stakeholders in Douglas County initiated a collective impact project to reform the county’s juvenile justice system. Since the first meeting of that group, a number of additional stakeholders have been incorporated into this initiative, which is now known as “Operation Youth Success.” Operation Youth Success, or OYS, has been engaged since that time in an effort to create system change producing a more effective, efficient, and compassionate justice system that better serves the families and youth who are the users of this system. This report will review the activities and progress of OYS through May of 2016